INTERVENSI AKTIVITAS FISIK TERHADAP KESEHATAN MENTAL REMAJA: KAJIAN LITERATUR - Qory Tifani Rahmatika (Poltekkes Kemenkes Malang, 2023)
Abstract: Adolescents are at risk of psychosocial problems and emotional regulation in their developmental years. One widely developed evidence-based intervention is physical activity. A recent literature review is needed to examine the effect of various physical activity interventions on mental health in adolescents. This article aims to determine the relationship between physical activity and mental health in adolescents. This article writing method used a literature review with online database search sources Google Scholar, Proquest and Science Direct conducted in 2013-2023. Eight articles that met the inclusion criteria in this literature review were obtained. Physical activity interventions are considered to positively impact improving mental health in adolescents with varying exercise intensities. The recommended types of physical activity include low-intensity physical activities such as yoga and tai-chi to high-intensity such as aerobic exercise, dancing, kickboxing, and resistance training. More research is needed on the effect of physical activity interventions on mental health problems that are more widespread in other age groups. Keywords: Adolescents, Literature Review, Mental Health, Mental Well-Being, Physcical Exercise